Probiotics – do they have a role in the pig industry? - M. Kenny; H. Smidt; E. Mengheri; B. Miller (Animal, 2011)
The delivery of certain living microorganisms in food has long been suggested as having positive health effects in humans. This practice has extended into food animal production, with a variety of microorganisms being used; lactic acid bacteria, various Bacillus species and the yeast Saccharomyces cerevisiae have been particularly used in the pig industry. The increased interest in probiotics is essentially due to the problem of microbial resistance to antibiotics and following the ban of the use of antibiotics in animal production, probiotics being considered an alternative means to reduce pathogen infection and improve animal health especially around the time of weaning. However, there is still a need to clarify the probiotic effectiveness in pigs, and the underlying mechanisms. When assessing the efficacy of probiotics one must consider the particular strain of organism being used and the production stage of the pigs being treated. The reproducible delivery of probiotics in industrial pig production is problematic as maintenance of viability is key to their beneficial activity, but difficult to achieve with commonly used feed processing technologies. One specific context where probiotics organisms may be reliably delivered is in systems utilising fermented liquid feeds. Liquid feed may be fermented by the activity of wild lactic acid bacteria or may be stimulated using specific isolates as ‘starters’; the latter system has advantages in terms of reproducibility and speed of fermentation. The farm context in which the organism is used is likely to be critical; the use of probiotics is more likely to result in measurable economic gains in animals living in sub-optimal conditions rather than in those reared in the highest welfare and husbandry conditions. The establishment of a beneficial lactic acid bacteria population at birth may lead to healthier animals, this may be most effectively achieved by treating sows, which provide an amplification step and flood the neonatal pigs’ environment with desirable bacterial strains. In contrast, it may be sufficient to provide a supportive, protective microbiota around the time of weaning as this is a time of major crisis with instability and loss of certain bacterial populations.